INFLUENCE OF CURING PARAMETERS ON CHEMICAL FIXATION AND WATER RESISTANCE OF MODIFIED BEECH VENEERS - Hien Mai, Trinh (Journal of Forestry Science and Technology, 2018)
In this study, Beech (Fagus sylvatica. L) sliced veneers with dimension of 37 × 0.5 × 50 mm3 (rad × tang × long) were soxhlet extracted with water and organic solvents (cyclohexan and ethanol, 2 : 1, v/v), and then oven-dried prior to the chemical impregnation. Three chemicals used for veneer impregnation were: N-methylol melamine (NMM - 1 - 10% solid content), fatty acid modified N-methylol melamine/paraffin compound (mNMM - 2 - 5% solid content), alkyl ketene dimer (AKD - 1% solid content). After 2 days of pre-drying in room condition, the impregnated veneers were cured in a hot press with different parameters of temperature and time. Specifically, temperature: 130°C, 160°C; pressure: 1 N/mm2; pressing time: 5, 10 and 20 min. The results indicated that influence of the hot pressing time and temperature on weight percent gain (WPG) and radial bulking effect (RBE), equilibrium moisture content (EMCR) and radial swelling (RS) in 20°C, 65% relative humidity, and weight losses after extraction did not showed detrimental effects in case of the veneers cured by hot pressing at 5 min and 130°C in comparison to the other hot pressing parameters. Besides, water repellent effectiveness (WRE) of the treated veneers after soxhlet with organic solvents and water submersion presented optimum results for the veneers cured by hot pressing at 5 min and 130°C. In addition, reduced time and temperature for curing of veneers may inhibit ‘over-drying’ of veneers before gluing process in production of plywood. Hence, the time of 5 minutes and the temperature of 130°C were selected for curing by hot press of the impregnated veneers. Effects of curing parameters (by hot press) on properties of veneer modified with each chemical were discussed in detail in this paper.